Policy content and stakeholder network analysis for infant and young child feeding in India - Seema Puri; Sylvia Fernandez; Amrita Puranik; Deepika Anand; Abhay Gaidhane; Zahiruddin Quazi Syed; Archana Patel; Shahadat Uddin; Anne Marie Thow (BMC, 2017)
Abstract Background Over the last decade, infant and young child feeding (IYCF) indicators in India have improved. However, poor IYCF practices are still apparent, associated with pervasive high rates of child under-nutrition. Interventions to improve IYCF need augmentation by appropriate policy support to consolidate gains. The aim of this study was to identify opportunities to strengthen and support IYCF policies through a policy content and stakeholder network analysis. Methods IYCF policies and guidelines were systematically mapped and coded using predetermined themes. Six 'net-map' group interviews were conducted for stakeholder analysis with data analyzed using ORA (organizational risk analyzer, copyright Carley, Carnegie Mellon University) software. The study was carried out at a national level and in the states of Maharashtra and unified Andhra Pradesh. Results Thirty relevant policy documents were identified. Support for IYCF was clearly apparent and was actioned within sectoral policies and strategic plans. We identified support for provision of information to mothers and caregivers in both sectoral and high-level/strategic policy documents. At a sectoral level, there was support for training health care workers and for enabling mothers to access IYCF. Opportunities to strengthen policy included expanding coverage and translating policy goals into implementation level documents. At the national level, Ministry of Women and Child Development [MoWCD], Ministry of Health and Family Welfare [MoHFW] and the Prime Minister's Nutrition Council [PMNC] were the most influential actors in providing technical support while MoHFW, MoWCD, and Bill Melinda Gates Foundation were the most influential actors in providing funding and were therefore influential stakeholders in shaping IYCF policies and programs. Conclusion We identified a wide range of strengths in the IYCF policy environment in India and also opportunities for improvement. One key strength is the integration of IYCF policies into a range of agendas and guidelines related to health and child development service delivery at the national and state level. However, the lack of a specific national policy on IYCF means that there is no formal mechanism for review and monitoring implementation across sectors and jurisdictions. Another opportunity identified is the development of IYCF policy guidelines in emergencies and for tribal populations.